2009
DOI: 10.3390/e11010085
|View full text |Cite
|
Sign up to set email alerts
|

The Insights of Algorithmic Entropy

Abstract: Abstract:The algorithmic entropy of a system, the length of the shortest algorithm that specifies the system's exact state adds some missing pieces to the entropy jigsaw. Because the approach embodies the traditional entropies as a special case, problematic issues such as the coarse graining framework of the Gibbs' entropy manifest themselves in a different and more manageable form, appearing as the description of the system and the choice of the universal computing machine. The provisional algorithmic entropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 47 publications
(88 reference statements)
0
23
0
Order By: Relevance
“…The relation between the above computer simulation information and the actual information intrinsic to the universe is analogous to the relation between the algorithmic information content (algorithmic entropy or Kolmogorov complexity), the size of the smallest algorithm that can generate a dataset and the actual amount of information contained within that dataset [64,65]. For non-random datasets algorithmic information is always less than the information in the dataset.…”
Section: Algorithmic Information Contentmentioning
confidence: 99%
“…The relation between the above computer simulation information and the actual information intrinsic to the universe is analogous to the relation between the algorithmic information content (algorithmic entropy or Kolmogorov complexity), the size of the smallest algorithm that can generate a dataset and the actual amount of information contained within that dataset [64,65]. For non-random datasets algorithmic information is always less than the information in the dataset.…”
Section: Algorithmic Information Contentmentioning
confidence: 99%
“…From this concept, we can introduce the t-time-Kolmogorov Complexity, or t-time-bounded algorithmic entropy [11].…”
Section: Algorithmic Entropymentioning
confidence: 99%
“…The Kolmogorov-Chaitin (KC, by acronym) as new tool possesses many applications, in fields as diverse as Combinatorics, Graph Theory, Analysis of Algorithms, or Learning Theory, among others [10,11].…”
Section: In At Most T(|x|) Steps}mentioning
confidence: 99%
“…Given that there are presently three "traditional understandings of entropy [which] include the thermodynamic approach of Clausius, the statistical mechanics approaches of Boltzmann and Gibbs and the information theory approach of Shannon" [1], it is still difficult to grasp the concept of entropy in an intuitive and straightforward way. It will be shown that connecting Clausius' understanding of entropy with information about mean values in the microscopic world coming out from the statistical approach, an uncomplicated representation of entropy arises, which readily lends itself to be pictorially visualized.…”
Section: Introductionmentioning
confidence: 99%